Di-μ-chlorido-bis{aquachlorido[3-ethyl-4-phenyl-5-(2-pyridyl)-4H-1,2,4-triazole-κ(2) N (1),N (5)]manganese(II)} - Wang, Zuoxiang (International Union of Crystallography, 2009)
In the centrosymmetric dinuclear title compound, [Mn(2)Cl(4)(C(15)H(14)N(4))(2)(H(2)O)(2)], the Mn(II) atom is coordinated by an N,N′-bidentate ligand, a water molecule, a terminal chloride ion and two bridging chloride ions in a distorted MnN(2)OCl(3) octahedral geometry. The Mn⋯Mn separation is 3.6563 (9) Å. In the crystal structure, O—H⋯N and O—H⋯Cl hydrogen bonds help to establish the packing.